Gambaran Employee Well-Being pada Karyawan dengan Sistem Kerja Hybrid di Yogyakarta - Margareta Putri Nugraheni; Metty Verasari (Lembaga Yasin AlSys, 2026)
Although hybrid work systems are increasingly being implemented in various organizations, studies that specifically describe the employee well-being (EWB) of employees working under a hybrid work system based on the dimensions of life well-being, workplace well-being, and psychological well-being still need to be strengthened. This study aims to describe EWB among employees with a hybrid work system in Yogyakarta and to analyze differences based on respondent characteristics. This study used a descriptive quantitative approach involving 422 respondents selected through purposive sampling. The research instrument used the Employee Well-Being Scale (EWBS) developed by Zheng, Zhu, Zhao, and Zhang (2015), which consists of 18 items. Data were analyzed using descriptive statistics and non-parametric difference tests, namely the Mann-Whitney U test, Kruskal-Wallis test, and Dunn’s post-hoc test. The results showed that, in general, the EWB of hybrid employees in Yogyakarta was classified as very high, with a mean score of 106.7, and 91.5% of respondents were in the high category. The psychological well-being dimension had the highest mean score of 35.82, followed by workplace well-being at 35.76, while life well-being obtained the lowest mean score of 35.13. Based on respondent characteristics, female employees had higher EWB than male employees, the 31–36-year age group had the highest EWB, employees of state-owned enterprises had the highest EWB compared with other types of employment, and employees with 1–3 years of service had the highest EWB. There were significant differences in EWB based on gender (p = 0.023), age (p = 0.001), type of employment (p < 0.001), and length of service (p < 0.001). The conclusion of this study affirms that the hybrid work system generally supports employee well-being. The implications of this study indicate the importance of organizational attention to vulnerable groups, particularly new employees with less than 6 months of service, young employees aged 19–24 years, and non-state-owned enterprise workers, so that the implementation of hybrid work systems can support employee well-being more equitably.